2015
DOI: 10.18488/journal.82/2015.2.4/82.4.46.65
|View full text |Cite
|
Sign up to set email alerts
|

Examined the Energy-Led Growth Hypothesis in India: Evidence from Time Series Analysis

Abstract: The present study examined the linkage between energy consumption and economic growth in India uses the annual time series data covering the period from 1970-71 to 2011-12. The study used Gross Domestic Product as a proxy for economic growth and energy consumption (oil equivalent per capital). The empirical findings of the study suggest that there is both the short run and the long run relationship exist between energy consumption and economic growth. The Granger causality result confirms that there is unidir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Initially, articles were selected with the help of keywords like 'energy', 'environment' and 'development'. Different studies that discuss the relationship between energy use and development have been drawn from across the world, but the majority of these relate to Asian countries (Zhang et al, 2012;Akhmat and Zaman, 2013;Ahmed and Long, 2014;Sehjpal et al, 2014;Cheng and Urpelainen, 2014;Behera, 2015;RECAP, 2017). We do not restrict the selection of articles to this region though Asian countries draw the attention of researchers for their high energy demand for the development and industrial activities (RECAP, 2017) and thus, there are plenty of articles that may be taken up for review.…”
Section: Review Planmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, articles were selected with the help of keywords like 'energy', 'environment' and 'development'. Different studies that discuss the relationship between energy use and development have been drawn from across the world, but the majority of these relate to Asian countries (Zhang et al, 2012;Akhmat and Zaman, 2013;Ahmed and Long, 2014;Sehjpal et al, 2014;Cheng and Urpelainen, 2014;Behera, 2015;RECAP, 2017). We do not restrict the selection of articles to this region though Asian countries draw the attention of researchers for their high energy demand for the development and industrial activities (RECAP, 2017) and thus, there are plenty of articles that may be taken up for review.…”
Section: Review Planmentioning
confidence: 99%
“…While exploring the relationship between economic growth and energy consumption, it was found that there was no uniformity across among developing countries regarding the causality between energy use and growth (Apergis and Payne, 2011; Shahateet, 2014;Wolde-Rufael, 2006;Behera, 2015). Even for the same country, results were found to differ across studies.…”
Section: Figure 1: Relation Between Energy Use and Growth Source: Conmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, electricity consumption and generation are both critical in altering economic success for not only being utilized as the prime input but also for influencing country's trade. Many studies argue that suitable and consistent energy supply is considered as an imperative pillar of industrial development and economic advancements of both developed and under developed nations (Morimoto and Hope, 2004;Ferguson et al, 2000;De Franchi and Boubaker, 2014;Behera, 2015;Ibrahim-Shwilima, 2016 Hwang andYoo, 2014). Hence, the vitality of energy is seen imperative to capture future growth, however, the negative consequences of energy are parallelly criticized for enhancing ecological pressure and abruption sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…In influencing the economic value (EVA): the measurement of accounting information -profitability, stability, growth, and activity -multiple regression analyses were conducted to verify the effect of the adjustment variables, which are conservative in the enterprise, the first stage verified the effects on the value of the entity (EVA): the second phase further introduced the adjustment variables of the entity, and the third phase put in the independent variables. The multiple coherence problems were analyzed by performing a standardization transformation (Balakeffi et al, 2019); (Behera, 2015); (Bendob et al, 2017).…”
Section: Research Hypothesismentioning
confidence: 99%